ANALISIS KINERJA KEUANGAN PERUSAHAAN DIDASARKAN PADA DU PONT SYSTEM - Prasetya, Hendra; Azizah, Nurul (JURNAL ILMIAH EDUNOMIKA, 2025)
Assessing financial performance is important for companies to stay competitive and grow sustainably. The Du Pont System evaluates profitability and asset use by analyzing key ratios. This helps identify factors that impact financial success. This research aims to analyze and evaluate the financial success of PT. Indofood CBP Sukses Makmur Tbk. over the years 2021-2023 by applying the Du Pont System methodology. Secondary data is utilized for this research. The result is that in 2023 the Return On Asset (ROA) value will be 7.10%, an increase from the previous year's 4.94% and the Return On Equity (ROE) value will be 13.63%, an increase from the previous year's 9.93%. The financial performance of PT has shown positive development. Indofood CBP Sukses Makmur tbk. can be considered to be performing well. The factors that need to be considered so that financial performance improves are the control and efficiency of expenses or costs which have an impact on achieving net profit.